Measuring Risk Aversion Model-Independently - Johannes Maier; Maximilian Rüger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
We propose a new method to elicit individuals' risk preferences. Similar to Holt and Laury (2002), we use a simple multiple price-list format. However, our method is based on a general notion of increasing risk, which allows classifying individuals as more or less risk-averse without assuming a specic utility framework. In a laboratory experiment we compare both methods. Each classies individuals almost identically as risk-averse, -neutral, or -seeking. However, classications of individuals as more or less risk-averse dier substantially. Moreover, our approach yields higher measures of risk aversion, and only with our method these measures are robust toward increasing stakes.
urn:nbn:de:bvb:19-epub-11873-7
Keywords: D81; C91; 330; Risk Aversion; Multiple Price-List; Elicitation; Laboratory Experiment; Holt and Laury Method; Mean Preserving Spreads; Non-EUT; Increasing Risk; Risikoaversion; Ökonomischer Anreiz; Messung; Test